Compensation and Community Corrosion: Perceived Inequalities, Social Comparisons, and Competition Following the Deepwater Horizon Oil Spill1. Issue 2 (June 2015) - Mayer, Brian; Running, Katrina; Bergstrand, Kelly
<x xml:space="preserve">Abstract</x> After disasters, victim compensation programs are typically associated with individual healing and community rebuilding. But postdisaster compensation systems also have the potential to introduce confusion and competition, further fraying the social fabric of communities affected by trauma. To assess the perceived effects of disaster compensation processes on community social relations, as well as the mechanisms that underlie such effects, we turn to the case of the Deepwater Horizon oil spill, after which BP implemented one of the largest compensation systems in U.S. history. Using data from interviews of residents of four Gulf Coast communities, we examine the extent to which this claims process hindered efforts to recover from this disaster. Our data suggest that while BP money helped some residents in the Gulf during a difficult economic time, many interviewees perceived uncertainty, randomness, and unevenness in the compensation process, which led to negative social comparisons and competition among community members. Because of this animosity, we argue that BP's compensation system was a disruptive mechanism that contributed to community corrosion and introduced another source of psychological stress into already‐traumatized areas.